2012
DOI: 10.3354/dao02408
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal structure and progression of growth anomalies in Porites australiensis in Okinawa, Japan

Abstract: Growth anomalies (GAs), one of the diseases recently reported for scleractinian corals, are characterized by an abnormal skeletal structure and reduced zooxanthella density. The pathological characteristics of GAs were studied in colonies of Porites australiensis on a reef in Kayo, Okinawa, Japan. Corallites in the GA region lost the skeletal architecture characteristic of P. australiensis, and polyp density had decreased in the GAs due to enlargement of both calices and the coenosteum. The gross productivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
(77 reference statements)
0
13
1
Order By: Relevance
“…However, previous field investigations demonstrated that GAs progressively spread toward healthy tissue on the host colonies (Cheney 1975, Bak 1983, Irikawa et al 2011, Yasuda et al 2012. Healthy fragments grafted to GA regions or fused with GA fragments exhibited reduced growth rates compared with non-grafted healthy fragments (Stimson 2010, Yasuda et al 2012. These findings suggest that GAs grow utilizing nutrient supplies from surrounding healthy regions (Yamashiro 2001et al, Domart-Coulon et al 2006, Yasuda et al 2012.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 36%
See 4 more Smart Citations
“…However, previous field investigations demonstrated that GAs progressively spread toward healthy tissue on the host colonies (Cheney 1975, Bak 1983, Irikawa et al 2011, Yasuda et al 2012. Healthy fragments grafted to GA regions or fused with GA fragments exhibited reduced growth rates compared with non-grafted healthy fragments (Stimson 2010, Yasuda et al 2012. These findings suggest that GAs grow utilizing nutrient supplies from surrounding healthy regions (Yamashiro 2001et al, Domart-Coulon et al 2006, Yasuda et al 2012.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 36%
“…(Hunter & Field 1997, Domart-Coulon et al 2006, Yasuda et al 2012, low lipid storage in M. informis (Yamashiro et al 2001), and low photosynthetic productivity in A. cytherea and P. australiensis due to reduced numbers of zooxanthellae in the gastrodermis (Irikawa et al 2011, Yasuda et al 2012. However, previous field investigations demonstrated that GAs progressively spread toward healthy tissue on the host colonies (Cheney 1975, Bak 1983, Irikawa et al 2011, Yasuda et al 2012. Healthy fragments grafted to GA regions or fused with GA fragments exhibited reduced growth rates compared with non-grafted healthy fragments (Stimson 2010, Yasuda et al 2012.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 82%
See 3 more Smart Citations